Polyvinylidene fluoride separation membrane and modification method thereof based on synergistic regulation of friction and mechanical force
Patent Information
- Application Number
- CN202511864731.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-11
AI Technical Summary
并且,该方法对阴离子染料的截留率提升,主要依赖于表面负电性的增强,当处理更复杂或电性不同的污染物时,其优势可能受限
[0021] As can be seen from the above technical solution, this solution modifies the PVDF separation membrane by using high-pressure liquid to impact the PVDF separation membrane while simultaneously applying a horizontal tensile force. PVDF separation membranes possess various crystal forms, including α, β, and γ phases. Among these, the β-phase molecular chains are arranged in an all-trans (TTTT) configuration with consistent dipole orientation, exhibiting strong polarity. Therefore, PVDF separation membranes dominated by the β-phase have good antifouling properties. In this application, during the solid-liquid friction process, a transient high-voltage micro-electric field is generated at the interface. Combined with the application of additional mechanical tensile force, this induces the transformation of the α-phase to the β-phase on the PVDF membrane surface. This crystal structure not only enhances the charge storage capacity of the PVDF membrane but also promotes the interaction between the membrane surface and water molecules, thereby improving hydrophilicity. Simultaneously, the increase in negative charge on the PVDF membrane surface enhances the electrostatic repulsion of anionic fuels such as Congo red, improving separation efficiency and significantly improving both the separation performance and antifouling performance of the PVDF membrane.
Smart Images

Figure CN121288583B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane modification technology, and in particular to a PVDF separation membrane and its modification method based on the synergistic regulation of friction and mechanical force. Background Technology
[0002] Polyvinylidene fluoride (PVDF), a polymer material with excellent chemical stability, high temperature resistance, and mechanical strength, has been widely used in the preparation of microfiltration and ultrafiltration membranes, playing an important role in the food industry, manufacturing industry, and chemical wastewater treatment. However, PVDF membranes have low surface energy, strong hydrophobicity, limited flux, and are prone to forming non-covalent interactions with pollutants, leading to severe membrane fouling, which greatly limits its application and promotion.
[0003] To address the antifouling problem of PVDF membranes, existing technologies mainly employ two methods: bulk modification and surface modification. Bulk modification requires the addition of hydrophilic additives or inorganic nanoparticles to the casting solution, while surface modification introduces hydrophilic groups through coatings, isoparticle deposition, ozone oxidation, etc. However, these methods all have significant drawbacks, requiring the introduction of additional chemical components, increasing manufacturing costs and process complexity. Some modification methods also suffer from functional degradation and may affect the membrane's microstructure and mechanical properties. Therefore, developing new modification methods for PVDF separation membranes is of great significance.
[0004] To address the aforementioned issues, the applicant previously proposed a physical modification method for PVDF separation membranes using high-pressure liquid impact in publication number CN119425405A. This method requires no chemical reagents and effectively enhances the membrane's hydrophilicity and surface negative charge through charge transfer and contact electrowetting effects generated by droplet friction, thereby improving water flux and dye rejection to some extent. However, further research and practice revealed inherent limitations to this technology: its modification effect is primarily concentrated on the membrane surface, achieved through physical adsorption or superficial chemical reactions, with minimal impact on the crystal structure of the PVDF material itself. This limits its performance improvement, particularly its long-term antifouling stability and charge storage capacity. Furthermore, the improved rejection rate of anionic dyes relies mainly on enhanced surface negative charge, and its advantages may be limited when treating more complex pollutants or those with different electrical charges. Summary of the Invention
[0005] To achieve the aforementioned surface-to-bulk phase modification, the inventors recognized a key technical challenge: how to transfer sufficient energy to the interior of the already formed, dense PVDF separation membrane to drive the coordinated rearrangement of molecular chains without causing mechanical damage. Simply relying on high-pressure liquid impact (i.e., the technology disclosed in CN119425405A) results in energy dissipation primarily at the surface, making it difficult to effectively penetrate the bulk phase. While mechanical stretching can act on the bulk phase, the large stretching ratio required to induce significant crystal transformation easily leads to membrane rupture, rendering it impractical. Therefore, it is necessary to propose a PVDF separation membrane and its modification method based on the coordinated regulation of friction and mechanical force, to achieve efficient and controllable reconstruction of the bulk crystal structure of the PVDF separation membrane without introducing exogenous chemical substances, thereby obtaining a PVDF modified membrane with superior performance, greater stability, and a more universal mechanism.
[0006] In a first aspect, the present invention provides a PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force. The method employs high-pressure liquid to impact the PVDF separation membrane while simultaneously applying a horizontal tensile force to the PVDF separation membrane. This induces the transformation of the α-crystal phase to the β-crystal phase on the surface of the PVDF membrane through the synergistic effect of solid-liquid friction and mechanical force, thereby achieving the modification of the PVDF separation membrane.
[0007] Preferably, the modification method specifically includes:
[0008] S1. Membrane pretreatment: Cut the PVDF base membrane into membrane sheets of a preset size;
[0009] S2. Applying mechanical force: The pre-treated membrane is laid flat and fixed, and one side of the membrane is clamped using a clamp. The clamp is connected to a tension gauge to apply a preset tension in the horizontal direction to the pre-treated membrane.
[0010] S3, High-pressure microdroplet friction treatment: A device consisting of a tensioned diaphragm and a tension gauge is placed under a high-pressure jetting device, and microdroplets are sprayed onto the diaphragm surface using the high-pressure jetting device;
[0011] S4. Synergistic modification by friction and mechanical force: After the droplets ejected by the high-pressure jet device stabilize, the device consisting of the membrane and the tension gauge that apply the tension is controlled to move horizontally, so that the microdroplets and the membrane surface can fully generate a high-voltage micro-electric field through solid-liquid friction. At the same time, combined with the additional mechanical tension, the α phase of the PVDF membrane surface is induced to transform into the β phase, thereby modifying the PVDF separation membrane.
[0012] Preferably, the preset tension is 0~3N.
[0013] Preferably, the tension is applied by horizontal uniform loading, and the tension is kept constant throughout the friction process after loading; and the horizontal movement direction of the device consisting of the diaphragm and the tension gauge is opposite to the horizontal component of the microdroplet ejection direction, so as to ensure that the diaphragm surface is in full contact with the microdroplets.
[0014] Preferably, the inclination angle between the nozzle of the high-pressure injection device and the diaphragm surface is 20~50°, and the vertical distance is 1~3cm.
[0015] Preferably, the nozzle material of the high-pressure injection device is one of 306 stainless steel, polyamide (PA), polyetheretherketone (PEEK), and polytetrafluoroethylene (PTFE).
[0016] Preferably, the pressure of the high-pressure liquid is 2~4 MPa.
[0017] Preferably, the high-pressure liquid is at least one of deionized water, acidic aqueous solution, salt solution and alkaline aqueous solution.
[0018] Preferably, the high-pressure liquid has a concentration of 0.5 × 10⁻⁶. -4 mol / L ~ 1.0 × 10 -4 A sodium hydroxide aqueous solution of mol / L.
[0019] In a second aspect, the present invention provides a PVDF separation membrane prepared by means of a PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force as described in any embodiment of the first aspect.
[0020] Preferably, the β-phase content of the modified PVDF separation membrane is increased by at least 6 percentage points compared with the untreated PVDF base membrane.
[0021] As can be seen from the above technical solution, this solution modifies the PVDF separation membrane by using high-pressure liquid to impact the PVDF separation membrane while simultaneously applying a horizontal tensile force. PVDF separation membranes possess various crystal forms, including α, β, and γ phases. Among these, the β-phase molecular chains are arranged in an all-trans (TTTT) configuration with consistent dipole orientation, exhibiting strong polarity. Therefore, PVDF separation membranes dominated by the β-phase have good antifouling properties. In this application, during the solid-liquid friction process, a transient high-voltage micro-electric field is generated at the interface. Combined with the application of additional mechanical tensile force, this induces the transformation of the α-phase to the β-phase on the PVDF membrane surface. This crystal structure not only enhances the charge storage capacity of the PVDF membrane but also promotes the interaction between the membrane surface and water molecules, thereby improving hydrophilicity. Simultaneously, the increase in negative charge on the PVDF membrane surface enhances the electrostatic repulsion of anionic fuels such as Congo red, improving separation efficiency and significantly improving both the separation performance and antifouling performance of the PVDF membrane. Attached Figure Description
[0022] Figure 1 The flowchart illustrates a PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force, as provided in an embodiment of the present invention.
[0023] Figure 2 This is a schematic diagram illustrating the implementation principle of the PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force provided in this embodiment of the invention. Detailed Implementation
[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] To address the problems of high cost, complex processes, and unstable performance associated with traditional modification methods, and to obtain high-performance, anti-fouling PVDF separation membranes, this invention considers employing high-pressure liquid impingement on the PVDF separation membrane while simultaneously applying a horizontal tensile force. This induces the α-phase to β-phase transformation on the PVDF membrane surface, combining triboelectric effect and mechanical force to achieve synergistic regulation of PVDF membrane performance. Specifically, as shown... Figure 1 As shown, the modification method may include the following steps:
[0026] S1. Membrane pretreatment: Cut the PVDF base membrane into membrane sheets of a preset size;
[0027] In this step, PVDF raw materials are prepared into PVDF-based membranes, cut into 6cm × 9cm sheets. The PVDF-based membranes are prepared using a phase inversion method: 12wt% PVDF and 7wt% polyethylene glycol are dissolved in N,N-dimethylacetamide to prepare a homogeneous casting solution. The mixture is then continuously stirred in a 65℃ water bath for 8 hours, followed by 24 hours of standing to remove bubbles. Further, the casting solution is uniformly coated onto a clean glass plate surface to form a film layer approximately 200μm thick. The glass plate is then immediately immersed in deionized water. After the membrane spontaneously peels off from the glass plate, it is further immersed for 24 hours to remove residual organic solvents and then refrigerated for later use.
[0028] Of course, in another embodiment, the PVDF base film can also be procured.
[0029] S2. Applying mechanical force: The pre-treated membrane is laid flat and fixed, and one side of the membrane is clamped using a clamp. The clamp is connected to a tension gauge to apply a preset tension in the horizontal direction to the pre-treated membrane.
[0030] like Figure 2 As shown, in this step, the tensile tester and the PVDF membrane are connected by clamps and springs, separated by a perforated wooden board to prevent liquid splashing during solid-liquid friction from affecting the accuracy of the test values. The tensile tester has a range resolution of 0.01N and a preset tensile force range of 0~3N. The entire device must be placed under the solid-liquid friction device to ensure that the friction and stretching processes are synchronized. When applying mechanical force, the cut membrane is laid flat on the wooden board to the left of the tensile tester. The right end of the membrane is connected to the tensile tester by clamps, and a horizontal tensile force (0, 1N, 2N, 3N) is applied to the membrane and kept constant throughout the solid-liquid friction process to keep the membrane molecular chains in a moderately stretched state.
[0031] In this embodiment, the tension is applied horizontally at a constant speed, and the tension remains constant throughout the friction process. The connection between the clamp and the diaphragm adopts a flexible buffer structure to avoid local stress concentration that could damage the diaphragm. Furthermore, the horizontal movement direction of the device consisting of the diaphragm applying the tension and the tension gauge is opposite to the horizontal component of the droplet ejection direction, ensuring that the diaphragm surface fully contacts the droplets and forms a uniform instantaneous high-voltage micro-electric field.
[0032] S3, High-pressure microdroplet friction treatment: A device consisting of a tensioned diaphragm and a tension gauge is placed under a high-pressure jetting device, and microdroplets are sprayed onto the diaphragm surface using the high-pressure jetting device;
[0033] In this step, the entire device consisting of the diaphragm and the force gauge after the tension is applied is placed into the solid-liquid friction device. The device is separated by a perforated wooden board to prevent the sprayed liquid from splashing onto the force gauge and affecting the measurement accuracy. A high-pressure jetting device is used to spray microdroplets onto the diaphragm surface. The tilt angle between the nozzle and the diaphragm surface can be 20°, 25°, 30°, 35°, 40°, 45°, or 50°, and the vertical distance can be 1cm, 2cm, or 3cm. The spraying solution can be deionized water, acidic aqueous solution, salt solution, or alkaline aqueous solution, and the spraying pressure can be 2MPa, 3MPa, or 4MPa.
[0034] When the high-pressure liquid is an alkaline aqueous solution, the high-pressure liquid can be a solution with a concentration of 0.5 × 10⁻⁶. -4 mol / L ~ 1.0 × 10 -4 A sodium hydroxide aqueous solution of mol / L.
[0035] The nozzle material of the high-pressure injection device can be 306 stainless steel, polyamide PA, polyether ether ketone PEEK, or polytetrafluoroethylene PTFE.
[0036] S4. Synergistic modification by friction and mechanical force: After the droplets ejected by the high-pressure jet device stabilize, the device consisting of the membrane and the tension gauge that apply the tension is controlled to move horizontally, so that the microdroplets and the membrane surface can fully generate a high-voltage micro-electric field through solid-liquid friction. At the same time, combined with the additional mechanical tension, the α phase of the PVDF membrane surface is induced to transform into the β phase, thereby modifying the PVDF separation membrane.
[0037] In this step, after the droplet ejection stabilizes, the membrane is controlled to move at a constant speed in the opposite direction to the horizontal component of the droplet ejection direction, ensuring that all areas of the membrane surface can fully contact the microdroplets. During the friction process of impact, expansion, contraction, and separation between the microdroplets and the membrane surface, an instantaneous high-voltage micro-electric field is generated. This electric field, together with the applied mechanical tension, works synergistically to induce the α-phase to β-phase transformation on the PVDF membrane surface.
[0038] In addition, the present invention provides a PVDF separation membrane, which is prepared by a PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force as described in any of the above embodiments.
[0039] Moreover, in one embodiment, the β-phase content of the modified PVDF separation membrane is increased by at least 6 percentage points compared to the untreated PVDF base membrane.
[0040] The effects of the present invention will be further explained below with reference to specific experiments.
[0041] I. Verification of the synergy between friction and mechanical force
[0042] The prepared uniform PVDF-based membrane was cut into three parts and subjected to the following tests: Example 1, Comparative Example 1, and Comparative Example 2. The PVDF-based membrane had a β-phase content of 50.38%, a contact angle of 90.2°, a Zeta potential of -18.9 mV, a Congo red rejection rate of 85.23%, and a pure water flux of 413.83 mV. .
[0043] (1) Example 1
[0044] The diaphragm is laid flat on the wooden platform to the left of the dynamometer. The right end of the diaphragm is connected to the dynamometer via a flexible clamp. A constant horizontal tension of 2N is applied, and the dynamometer monitors and maintains the tension in real time. The above device is placed under a solid-liquid friction device, with a 1.0×10⁻⁶ ohmmeter. -4 A mol / L sodium hydroxide aqueous solution was used as the spray liquid. The nozzle of the high-pressure spray device was at a 30° angle to the membrane surface, with a vertical distance of 2 cm, and the spray pressure was set to 3 MPa. After the liquid spray stabilized, the membrane was moved at a speed of 5 mm / s in the opposite direction to the horizontal component of the spray direction, and the friction treatment time was 1 min. After the test was completed, the membrane was removed, placed in a petri dish for moist storage, and then subjected to performance testing.
[0045] (2) Comparative Example 1
[0046] The only difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not apply mechanical tension, but only performs a single friction treatment; the remaining steps are exactly the same as in Example 1. It should be noted that Comparative Example 1 is the technical solution previously applied for by the applicant as described in the background art.
[0047] (3) Comparative Example 2
[0048] The only difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not undergo high-pressure microdroplet friction treatment, but only mechanical tensile treatment; the remaining steps are exactly the same as in Example 1.
[0049] The performance of the PVDF separation membranes obtained in Example 1, Comparative Example 1, and Comparative Example 2 was tested, and the results are shown in Table 1 below:
[0050] Table 1
[0051] Analysis: Based on the above results, applying additional tension without friction has almost no effect on the performance of the PVDF membrane, while friction alone significantly alters its properties. The modification method involving applying an additional 2N tension combined with friction has the greatest impact on the PVDF membrane. This is mainly because a single tensile physical field has little effect on the already formed PVDF membrane. However, during high-pressure microdroplet friction, a transient high voltage is generated at the micro-interface, forming a micro-electric field that synergistically promotes the formation of the β phase within the membrane. Simultaneously, oxidation reactions also occur during high-pressure microdroplet friction, synergistically enhancing the contact electrowetting effect, increasing the negative potential of the PVDF membrane surface and the β phase content, further improving the membrane's water flux and anionic Congo red dye rejection rate.
[0052] Specifically, Comparative Example 1 (i.e., simulating existing technology CN119425405A, only subjecting to high-pressure liquid impact) can improve the β-phase content and hydrophilicity and separation performance to some extent, but its modification of the bulk crystal structure (β-phase) is limited (only an increase of 1.02 percentage points), resulting in a bottleneck in performance improvement. In contrast, the friction + tension synergistic method provided by this invention (Example 1), under the same liquid, pressure, and time parameters, achieves efficient reconstruction of the PVDF membrane bulk phase structure by simultaneously applying a horizontal tension of only 2N: the increase in β-phase content (6.76 percentage points) is more than 6.6 times that of Comparative Example 1 (1.02 percentage points); more importantly, the membrane's water flux and Congo red rejection rate are simultaneously and significantly improved. This result completely breaks the permeability-selectivity trade-off effect commonly found in the field of membrane separation. For example, in Example 1, while further increasing the Congo red rejection rate of Comparative Example 1 from 90.98% to 92.35%, the water flux also increased from 470.34 to 487.92. (Simultaneous improvement in permeability) achieves synergistic optimization of both, breaking through the traditional limitation of a trade-off between the two. This phenomenon indicates that the simultaneously applied micro-mechanical tension is not a simple auxiliary means, but rather produces a profound synergy with the high-voltage triboelectric effect. The tension lowers the energy barrier of conformational transformation at the molecular level, allowing the micro-electric field generated by friction to more effectively drive the rearrangement of bulk molecular chains, thereby achieving a qualitative change from surface modification to bulk reconstruction under extremely low mechanical load. The results of Comparative Example 2 (applying only 2N tension) further demonstrate that without the guidance of the triboelectric field, simple micro-tension is almost ineffective for the already formed dense film structure.
[0053] Therefore, although mechanical stretching alone may induce crystal transformation, it typically requires a large stretching ratio and has limited effect on already formed thin films. Furthermore, the electric field effect of high-voltage triboelectric charging alone lacks sufficient energy for bulk crystal transformation. The synergistic effect of this invention lies in the fact that the triboelectric micro-field provides directional guidance for dipole rearrangement, while the simultaneous small tensile force provides mechanical assistance for molecular chain extension and barrier reduction. Both are indispensable, thus achieving a highly efficient crystal transformation under low mechanical stress conditions.
[0054] In summary, the simultaneous introduction of a small horizontal tensile force within a specific range (0-3N) during the known physical modification process of high-pressure liquid impact in this invention is not a simple process adjustment, but rather a profound physical synergy that transforms the modification mechanism from surface physicochemical interaction to bulk crystal structure reconstruction. This synergistic qualitative change, and the resulting performance improvement several times greater than that of existing technologies, is not readily apparent to those skilled in the art based on prior art.
[0055] II. The Influence of Different Nozzle Materials on Performance
[0056] (1) Example 1
[0057] In Example 1, the nozzle of the high-pressure injection device is made of the original material, which is 306 stainless steel.
[0058] (2) Example 2
[0059] The only difference between Example 2 and Example 1 is that the nozzle of the high-pressure injection device in Example 1 is made of the original material, while in Example 2 the nozzle is replaced with polyamide PA material.
[0060] (3) Example 3
[0061] The only difference between Example 3 and Example 1 is that the nozzle of the high-pressure injection device in Example 1 is made of the original material, while in Example 3 the nozzle is replaced with polyetheretherketone (PEEK) material.
[0062] (4) Example 4
[0063] The only difference between Example 4 and Example 1 is that the nozzle of the high-pressure injection device in Example 1 is made of the original material, while in Example 4 the nozzle is replaced with polytetrafluoroethylene (PTFE).
[0064] The modified PVDF separation membranes prepared according to the methods described in Examples 1 to 4 above were subjected to performance tests, and the test results are shown in Table 2 below.
[0065] Table 2
[0066] Analysis: Under high-voltage electric field and mechanical tension, the β-phase content inside the PVDF membrane increases, polarization is enhanced, and more negative charges are stored. Based on the triboelectric properties of the materials, PTFE readily gains electrons, resulting in positively charged droplets; while PA readily loses electrons, resulting in negatively charged droplets. Experimental results show that using a PA nozzle resulted in the most significant decrease in the contact angle and the largest increase in the negative value of the Zeta potential, indicating the most outstanding surface modification effect. This may be because under the impact of high-voltage droplets, effective charge transfer and surface potential regulation occur between the negatively charged droplets and the PVDF membrane surface. It also promotes the attack of OH- ions in the droplets on the CF bonds of the PVDF surface, leading to defluorination and oxidation reactions. Therefore, the PA nozzle has the best modification effect on the PVDF membrane. The modified PVDF membrane showed a simultaneous increase in both the water flux and rejection rate for the anionic dye Congo red, verifying the effectiveness of this method.
[0067] In summary, based on the above experimental results, the triboelectric-mechanical synergistic mechanism revealed in this invention can be systematically explained as a breakthrough of the limitations of prior art (CN119425405A): prior art only touches upon mechanism (2) (charge transfer) and part of mechanism (3) (contact electrowetting), and its effect ends at the surface. The synergistic effect of this invention is that, firstly, it achieves efficient induction of bulk crystal form through mechanism (1); then, the newly grown β phase structure greatly enhances the stability of charge storage through mechanism (2); finally, the stable bulk polarity and charge work together to bring better and more durable hydrophilicity and separation performance through mechanisms (3) and (4). This is a cascade enhancement process that is interconnected and goes from the surface to the core, and its starting point and core is the synergistic induction of crystal form transformation. Thus, the two complement each other through mechanism and superimpose efficiency to achieve precise control of the crystal structure and performance of PVDF film. Specifically, the synergistic effect mechanism (1)~(4) is analyzed as follows:
[0068] (1) Synergistic Induction Mechanism of Crystal Transformation: The transformation from α phase to β phase in PVDF films is essentially a transformation of the molecular chain conformation from a side-side arrangement to an all-trans arrangement, which requires overcoming a certain energy barrier and achieving directional arrangement of dipoles. On the one hand, during the high-pressure microdroplet friction process, the intense impact and separation between the droplet and the film surface generates an instantaneous high-pressure micro-electric field. This electric field generates a directional driving force on the dipoles of the PVDF molecular chains, forcing the dipoles to align regularly along the direction of the electric field, providing thermodynamic conditions for the formation of the β phase. On the other hand, the applied mechanical tension causes the PVDF molecular chains to extend along the direction of the tension, reducing the spatial steric hindrance between the molecular chains and lowering the energy barrier for conformational transformation. At the same time, the tensile stress directly promotes the transformation of the molecular chains from a loose α phase conformation to a compact and ordered β phase conformation. Under the synergistic effect of the two, the crystal transformation efficiency is significantly improved. For example, when the tension is 2N, the β phase content is significantly increased, and the β phase distribution is more uniform, avoiding the problem of incomplete local crystal transformation caused by single electric field treatment.
[0069] (2) Synergistic enhancement of charge storage and surface charge: The β-crystalline PVDF molecular chains have consistent dipole orientation and extremely strong charge storage capacity, which provides a structural basis for charge retention during the friction process. Electron transfer generated by high-pressure microdroplet friction increases the negative charge on the film surface, while the synergistically induced β-phase structure captures and stabilizes these charges through dipole polarization, reducing charge dissipation; at the same time, mechanical tension causes the molecular chains to extend, increasing the charge adsorption sites and further enhancing the surface negative charge density. Under the synergistic effect, the Zeta potential of the PVDF film decreases significantly, the surface negative charge is significantly enhanced, and the charge stability is greatly improved.
[0070] (3) Synergistic effect of improved hydrophilicity: The strong polarity of the β-phase significantly enhances the interaction between the PVDF membrane surface and water molecules, forming a stable hydration layer through hydrogen bonding. Simultaneously, the electrowetting effect generated by charge transfer during friction, combined with the polarity of the β-phase, further reduces the contact resistance of water molecules on the membrane surface. Mechanical tension optimizes the microstructure of the membrane surface, slightly increasing the roughness and thus the contact area between the membrane surface and water molecules, promoting the formation of the hydration layer. Under this synergistic effect, the contact angle of the membrane surface decreases significantly, hydrophilicity is significantly improved, and the presence of the hydration layer effectively hinders the direct adsorption of pollutants to the membrane surface, fundamentally improving antifouling performance.
[0071] (4) Synergistic optimization of separation performance: The significantly enhanced negative charge on the modified membrane surface generates a strong electrostatic repulsion with anionic dye molecules such as Congo red and methylene blue, reducing the adsorption of dye molecules on the membrane surface and pore blockage, and improving the rejection rate; the enhanced hydrophilicity brought about by the β phase structure reduces the mass transfer resistance of water, and significantly increases the water flux.
[0072] The modules or units in the device of this invention can be merged, divided, and deleted according to actual needs. The above-disclosed embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of the invention. Those skilled in the art will understand that implementing all or part of the processes of the above embodiments and making equivalent changes according to the claims of this invention still fall within the scope of the invention.
Claims
1. A method for modifying PVDF separation membranes based on the synergistic regulation of friction and mechanical force, characterized in that, A high-pressure liquid is used to impact the PVDF separation membrane while simultaneously applying a horizontal tensile force. This induces a transformation of the α-crystalline phase to the β-crystalline phase on the PVDF membrane surface through the synergistic effect of solid-liquid friction and mechanical force, thereby modifying the PVDF separation membrane. The high-pressure liquid has a concentration of 0.5 × 10⁻⁶. -4 mol / L ~ 1.0 × 10 -4 A sodium hydroxide aqueous solution of mol / L; the modification method specifically includes: S1. Membrane pretreatment: Cut the PVDF base membrane into membrane sheets of a preset size; S2. Applying mechanical force: The pre-treated membrane is laid flat and fixed, and one side of the membrane is clamped using a clamp connected to a tension gauge to apply a preset tension of 1~3N in the horizontal direction to the pre-treated membrane. S3. High-pressure microdroplet friction treatment: A device consisting of a tensioned diaphragm and a tension gauge is placed under a high-pressure jetting device, which then sprays microdroplets onto the diaphragm surface. The nozzle of the high-pressure jetting device is made of one of the following materials: polyamide (PA), 306 stainless steel, polyetheretherketone (PEEK), or polytetrafluoroethylene (PTFE). The inclination angle between the nozzle and the diaphragm surface is 20-50°, and the vertical distance is 1-3 cm. S4. Synergistic modification by friction and mechanical force: After the droplets ejected by the high-pressure jet device stabilize, the device consisting of the membrane and the tension gauge that apply the tension is controlled to move horizontally, so that the microdroplets and the membrane surface can fully generate a high-voltage micro-electric field through solid-liquid friction. At the same time, combined with additional mechanical tension, the α phase on the PVDF membrane surface is induced to transform into the β phase, thereby modifying the PVDF separation membrane.
2. The PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force according to claim 1, characterized in that, The tension is applied in a horizontal uniform loading manner, and the tension is kept constant throughout the entire friction treatment process after loading; and the horizontal movement direction of the device consisting of the diaphragm and the tension gauge is opposite to the horizontal component direction of the microdroplet ejection direction, so as to ensure that the diaphragm surface is in full contact with the microdroplets.
3. The PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force according to claim 1, characterized in that, The pressure of the high-pressure liquid is 2~4MPa.
4. A PVDF separation membrane, characterized in that, The PVDF separation membrane was prepared using the PVDF separation membrane modification method based on the synergistic regulation of friction and mechanical force as described in any one of claims 1-3.
5. The PVDF separation membrane according to claim 4, characterized in that, The modified PVDF separation membrane has a β-phase content that is at least 6 percentage points higher than that of the untreated PVDF base membrane.
Citation Information
Patent Citations
Preparation method of PVDF (Polyvinylidene Fluoride) film with high beta crystal content
CN114106373A
Modification method of PVDF (Polyvinylidene Fluoride) separation membrane
CN119425405A